2022
DOI: 10.1021/acsaem.2c02663
|View full text |Cite
|
Sign up to set email alerts
|

Li-Ion Diffusion Correlations in LiAlGeO4: Quasielastic Neutron Scattering and Ab Initio Simulation

Abstract: We investigated the impact of Li stoichiometry and host flexibility on Li+ diffusion processes in LiAlGeO4 at the microscopic level using quasielastic neutron scattering (QENS) and ab initio molecular dynamics (AIMD) simulations. Using sufficiently long AIMD trajectories, we could simulate the observed QENS signal and identify the localized dynamics of Li in crystalline LiAlGeO4. Such information is vital to identify the bottleneck of diffusion processes and design materials for battery application. Our AIMD s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…DFT calculations indicated that organic Reproduced with permission: Copyright 2022, American Chemical Society. [80] | 355 ligand with multiple active sites had a higher theoretical capacity. Given that Co(II) possesses more electrons near the Fermi level compared to Ni(II), Co-OPCA demonstrates a higher electron density, allowing each structural unit to bind with more lithium ions, thereby enhancing lithium storage performance.…”
Section: Theoretical Capacitymentioning
confidence: 99%
See 2 more Smart Citations
“…DFT calculations indicated that organic Reproduced with permission: Copyright 2022, American Chemical Society. [80] | 355 ligand with multiple active sites had a higher theoretical capacity. Given that Co(II) possesses more electrons near the Fermi level compared to Ni(II), Co-OPCA demonstrates a higher electron density, allowing each structural unit to bind with more lithium ions, thereby enhancing lithium storage performance.…”
Section: Theoretical Capacitymentioning
confidence: 99%
“…Utilizing AIMD to calculate the theoretical diffusion coefficients of materials plays a crucial role in assessing the material's influence on lifespan and constructing multiscale models. Kumar et al [ 80 ] employed AIMD simulations to investigate the diffusion of Li + in LiAlGeO 4 (LAGO) compounds under various engineering strategies, including crystalline, with vacancies, with excess Li (exc‐LAGO), and in amorphous structures. AIMD simulations provide a detailed microscopic understanding of the lithium diffusion process and the key structural and dynamic features associated with lithium diffusion.…”
Section: Multiscale Modeling From Atomic To Cellmentioning
confidence: 99%
See 1 more Smart Citation